Immunogenicity of singlet oxygen modified human DNA implications for anti-DNA antibodies in systemic lupus erythematosus - Al Arfaj, Abdurahman Saud (Clinical immunology (Orlando, Fla.), 2007)
Reactive oxygen species (ROS)-modified DNA has been shown to be a better and more discriminating immunogen than native DNA (nDNA) for the production of anti-DNA autoantibodies in SLE (systemic lupus erythematosus). Among ROS, the role of hydroxyl radical (.OH) in the induction of damage and modification of nDNA has been extensively studied while such documentation implicating singlet oxygen ((1)O(2)) in inducing immunogenicity in nDNA leading to the production of anti-double-stranded (ds) DNA autoantibodies in SLE is not yet available. This prospective study was undertaken to evaluate the immunogenicity of healthy human dsDNA modified with (1)O(2) generated by methylene blue plus radiant light. Female rabbits were immunized with (1)O(2)-modified human dsDNA to raise anti-dsDNA antibodies. (1)O(2)-modified anti-dsDNA rabbit immune sera and the (1)O(2)-modified anti-dsDNA rabbit purified immunoglobulin G (IgG) were tested against a variety of dsDNA antigenic substrates through direct enzyme-linked immunosorbent assay (ELISA). The immunogenicity of (1)O(2)-modified human dsDNA was further evaluated by studying its immunoreactivity with SLE patients' sera and SLE patients' purified anti-dsDNA IgG. As compared to healthy human sera, (1)O(2)-modified anti-dsDNA rabbit immune sera as well as the (1)O(2)-modified anti-dsDNA rabbit purified IgG demonstrated a strong affinity towards (1)O(2)-modified human dsDNA(.)(1)O(2)-modified human dsDNA proved to be potentially more immunogenic against SLE patients' whole sera and SLE patients' purified IgG as compared to healthy human sera. Our findings suggest that (1)O(2) may also be inducing immunogenicity in native dsDNA resulting in the production of anti-dsDNA autoantibodies as seen in SLE patients